Efficacy of Flexibility Exercise for Subjects with Achilles Tendinitis- Quasi-Experimental Study. - Ranjith M.; Anitha A.; Ramana K.; Kamalakannan M. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Achilles tendinitis is a habitual overuse injury, particularly in the field of sports which may involve lunging and jumping activities. This study focuses on how well brief flexibility exercises help subjects with Achilles Tendinitis and improves their functional activity and decreases the pain. Purpose: The Purpose of the study is to determine the effect of flexibility exercise in reducing pain and in improving functional activity among subjects with Achilles tendinitis. Materials and Methods: This is a Quasi-Experimental study where subjects with Achilles Tendinopathy were selected on the basis of the selection criteria. The subjects were briefed about the procedure and informed consent was acquired. Pre-test scores for pain and functional ability were recorded using NPRS and VISA, the same as post-test values after 4 weeks of intervention. The entire process was performed from November 2022 to March 2023. Result: From the test values according to the VISA and NPRS it results that flexibility exercise for Achilles tendinitis helps in reducing pain and it gives the best result in improving functional activity. Conclusion: According to the data gathered, flexibility training for four weeks with twelve sessions enhances physical activity and reduces discomfort in patients with Achilles tendinopathy.